Empowering Translators through Entrepreneurship in Simulated Translation Bureaus - van Egdom, Gys-Walt; Konttinen, Kalle; Vandepitte, Sonia; Fernández-Parra, María; Loock, Rudy; Bindels, Joop (HERMES - Journal of Language and Communication in Business, 2020)
This paper reviews entrepreneurial activities that take place within the simulated translation bureaus of member institutions of the INSTB network and establishes a link between entrepreneurism, self-efficacy and perceived competence. Reusing pre-test and post-test data of a student survey, a first attempt is made to design and test a survey instrument for gauging the impact of a simulated translation bureau on perceived entrepreneurial competence and self-efficacy for planning, setting up, and managing a translating organisation in pedagogical translation company simulations. Tentative results suggest a positive effect of participation in translation company simulation modules on students’ entrepreneurial self-efficacy and perceived competence. Because of the anonymity of the data, pre-test and post-test responses could not be paired. As a consequence, the statistical significance of the results could not be confirmed.